Learning Entrepreneurs Early Childhood to Increase the Attitude of Childrens Children In Khalifah History Sukonandi Yogyakarta - Safitri, Alisa Eriyani; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2017)
The purpose of this study is to describe the Learning of Entrepreneurship of AUD to improve the attitude of child self-reliance in kindergarten Khalifah Sukonandi Yogyakarta, as well as supporting factors and inhibiting the attitude of independence of children through entrepreneurial learning in kindergarten Khalifah Sukonandi Yogyakarta. This research is a qualitative research by using the method of observation, interview, and documentation in collecting data. Data analysis technique with interactive model. Data validity uses triangulation of methods and sources. Based on the results of data analysis conducted, the implementation of the entrepreneurship learning of AUD in TK Khalifah Sukonandi Yogyakarta includes: the initial activities, core activities, rest and cover. Children perform dhuha prayers together, where it is the way that is done to instill the value of successful entrepreneurs in the childs self by praying dhuha before learning begins. Because by training a child praying dhuha there is a value of discipline which is one of the values ââof entrepreneurship. General learning activities with centers and there are special activities for entrepreneurship, such as market day, outing class and cooking class. Children look spirit and child independence attitude is good in offering merchandise. Childrens collaboration is good where children remind each other of their friends when choosing food or drink taken. In the implementation adjust the theme and conditions. For the special activities of market day TK Khalifah Sukonandi Yogyakarta made a semester program and the process of preparing a daily activity plan is incorporated into learning such as role play. The curriculum is centralized and distributed in the finished form. Teachers develop their own activities that will be implemented and adapted to the situation. Cooking class activity done twice a month. Market day activity is done three times. Outing activities are conducted two to three times. The factors supporting child self-reliance through entrepreneurship learning include: (1) from their own children, (2) the relationship between teachers and students, (3) good teamwork between teachers and (4) geographical location. Inhibiting factors of child self-reliance through entrepreneurial learning include: (1) limited places for outing, (2) limited number of children in market day activities, (3) limited educational game tools.